Health Insurance in the United States of America : Austrian Perspectives on Interventionism before ObamaCare - Jasiński, Łukasz (Routledge focus on economics and finance., 2025)
The U.S. health care system is dominated by private and public (governmental) insurance which makes it difficult for many Americans to imagine access to health care without it. The health care system in the USA is sometimes mistakenly referred to as market-based, partly because of the previous lack of compulsory insurance.As this book shows, however, even before ObamaCare it was a system heavily influenced by the government. This short and accessible book demonstrates that governmental long-term interventionism in the American health insurance market has led to many contemporary serious problems, such as significant and uncontrolled increases in health care costs, rising health insurance prices, marginalization of direct payments, limited competition, and problems with uninsured Americans. Many observers wrongly blame the market for this state of affairs and demand more regulation, which further deteriorates the situation. The study is divided into two parts: an analysis of the history of interventions (and their effects) in the private health insurance market, and an analysis of the genesis and evolution of governmental Medicare and Medicaid insurance. Thus, the book constitutes a unique synthesis of Austrian theory of interventionism and the history of health insurance in the USA.This book is vital reading for health economists, managers, and policymakers, as well as those interested in the Austrian approach to economics.